2012
DOI: 10.1021/jm2013369
|View full text |Cite
|
Sign up to set email alerts
|

Acylthiourea, Acylurea, and Acylguanidine Derivatives with Potent Hedgehog Inhibiting Activity

Abstract: The Smoothened (Smo) receptor is the major transducer of the Hedgehog (Hh) signaling pathway. On the basis of the structure of the acylthiourea Smo antagonist (MRT-10), a number of different series of analogous compounds were prepared by ligand-based structural optimization. The acylthioureas, originally identified as actives, were converted into the corresponding acylureas or acylguanidines. In each series, similar structural trends delivered potent compounds with IC(50) values in the nanomolar range with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 45 publications
2
59
0
Order By: Relevance
“…We first tested these compounds at a large range of doses in NIH3T3 cells stably transfected with a Gli-dependent firefly luciferase reporter (Taipale et al, 2000). This mouse embryonic fibroblast cell line has been widely used for measuring Hh signaling activity through Smo (Solinas et al, 2012). We observed that, as expected (Masdeu et al, 2006), SAG potently stimulated Hh reporter gene transcription with an EC 50 of ∼0.15 mM, whereas GSA-10 displayed no stimulatory effect, even at 10 mM (Fig.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…We first tested these compounds at a large range of doses in NIH3T3 cells stably transfected with a Gli-dependent firefly luciferase reporter (Taipale et al, 2000). This mouse embryonic fibroblast cell line has been widely used for measuring Hh signaling activity through Smo (Solinas et al, 2012). We observed that, as expected (Masdeu et al, 2006), SAG potently stimulated Hh reporter gene transcription with an EC 50 of ∼0.15 mM, whereas GSA-10 displayed no stimulatory effect, even at 10 mM (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…The concentration of SAG and GSA-10 used in these experiments was near their respective EC 50 . The potent Smo antagonist MRT-83 (Roudaut et al, 2011;Solinas et al, 2012) displayed a similar potency to block Virtual Screening-Based Discovery of GSA-10 GSA-10 (1 mM) and SAG (0.1 mM) response (IC 50 , ∼38 and 11 nM, respectively) (Fig. 7, B and C).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…In the 1 H NMR spectrum, the signal of thiourea NH proton adjacent the phenyl ring of 1 and 2 is located in the far down field (11.67 and 12.91 ppm in CD 3 Cl solution), which can be attributed to the strong intramolecular hydrogen bond formation in 1 and 2 (see below). Strong intramolecular hydrogen bond is often observed in acylthiourea ligands [56].…”
Section: Resultsmentioning
confidence: 99%